Toleransi Dalam Pandangan Imam Mazhab Dan Ulama Kontemporer Perspektif Hukum Islam - Anwar, Syaiful; Fauzi, Muhammad; Yani, Ahmad; Siswoyo, Siswoyo (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
Tolerance is an important concept in Islam that reflects respect for differences and diversity in society. This study aims to analyze the views of the Imams of Madzhab and contemporary scholars regarding tolerance in the perspective of Islamic law. Through a qualitative approach, data is obtained from literature studies and relevant primary sources. The results of the study show that tolerance has a significant meaning in Islam, with the importance of respecting and understanding differences within the framework of Islamic law. The views of the Imams of the Sunni School, such as Abu Hanifah, Malik, Shafi'i, and Ahmad bin Hanbal, as well as the views of the Imams of the Shiite School, such as Ja'far Sadiq, Muhammad Baqir, and Ali Rida, show understanding and support for tolerance. Contemporary Sunni and Shia scholars also provide views that are in line with the previous Imams of the School, emphasizing the importance of tolerance in building a harmonious and respectful society. Through case studies of contemporary clerics, there are real efforts to promote tolerance, both through preaching, inter-religious dialogue, and social activities that involve cross-faiths.